Heavy-metal remediation by a fungus as a means of production of lead and cadmium carbonate crystals - Sanyal, A.; Rautaray, D.; Bansal, Vipul; Ahmad, Absar; Sastry, Murali (Langmuir, 2005)
We show here that reaction of the fungus, Fusarium oxysporum, with the aqueous heavy-metal ions Pb2+ and Cd2+ results in the one-step formation of the corresponding metal carbonates. The metal carbonates are formed by reaction of the heavy-metal ions with CO2 produced by the fungus during metabolism and thus provide a completely biological method for production of crystals of metal carbonates. The PbCO3 and CdCO3 crystals thus produced have interesting morphologies that are shown to arise because of interaction of the growing crystals with specific proteins secreted by the fungus during reaction. An additional advantage of this approach is that the reaction leads to detoxification of the aqueous solution and could have immense potential for bioremediation of heavy metals. Under conditions of this study, the metal ions are not toxic to the fungus, which readily grows after exposure to the metal ions.